Psychological Impact of Religious and Spiritual Beliefs on Life Quality of Two groups of University Students - Younis, Maha S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background; this study is designed to assess the effect of religious and spiritual beliefs on quality of life among two groups of university students in Iraq and Jordan.Objective: to examine the psychological impact of religious and spiritual beliefs on quality of life and to implement the Quality of Life- Spiritual Religious and Personal Beliefs(QOL-SRPB)questionnaire for the first time in both countries .Method :A convenient sample of advanced medical students from Baghdad college of Medicine in Iraq and College of Medicine in University of Science and Technology in Jordan recruited during April 2008 to complete 200 forms of the Arabic modified version of QOL-SRPB simultaneously.Results: Analysis of the findings revealed higher measures of importance regarding spirituality in the Jordanian group in comparison to the Iraqi group; however, comparable mean scores of all facets were reported in both groupsConclusion:. Both studied groups showed comparable results due to the presence of shared belief system and cultural norms .despite the circumstantial hardship of the Iraqi group they showed reasonable satisfaction to their quality of life.